Edukasi Kesehatan Dengan Media Leaflet Tentang Menopause Pada Kelompok Ibu PKK Di BTN Pagesangan Kecamatan Mataram - Risa Arieska (Universitas Pahlawan Tuanku Tambusai, 2022)
Health services at productive age are health services for every citizen aged 15 to 59 years in the form of education and health screening in their working area within one year. Productive age health services according to standards include health education including family planning and screening for risk factors for communicable and non-communicable diseases. Educational services at productive age are carried out at Health Service Facilities and/or UKBM. Risk factor screening services at productive age are carried out at least once a year, one of which is anamnesa of risky behavior. Risky behavior arises from the perception of society (especially mothers) who consider menopause as a frightening time. There are still many people (mothers) who do not understand menopause, its causes, symptoms and factors that influence menopause symptoms. People (mothers) are reluctant to ask health workers about menopause and its consequences. Many people (mothers) still don't know how to live a healthy life during menopause. The framework of the problem is the provision of counseling to increase knowledge about menopause, signs and symptoms, trigger factors, and menopausal lifestyle. Providing health education about lifestyle and diet arrangements to prevent comorbidities during menopause. The existence of health education can reduce the risk of non-communicable diseases that arise from risky behavior and this has an impact on increasing life expectancy making the population of the elderly group even greater. Realization that has been done includes health counseling with lectures about menopause and various diseases that accompany menopause as well as counseling about lifestyle that must be done in facing menopause. The results obtained from this health education activity turned out that PKK mothers really need correct and appropriate information about menopause, because if mothers do not have sufficient knowledge and will have wrong perceptions or think menopause is a scary time and anxiety will arise which will result in the emergence of various non-communicable diseases or accompanying infectious diseases during menopause. Keywords: Health Education, Leaflet, Knowledge, Mennopause